Methods for reducing the environmental impact of rock mass excavation - Jug, Jasmin; Grabar, Kristijan (2020)
Many engineering projects and interventions have negative effects on the environment. Rock excavation in civil engineering, either in mining or in construction, often is unthinkable without the use of explosive. However, blasting can have extensive adverse environmental impacts, like vibrations, noise, dust and chemical contamination. Therefore, it is better to avoid blasting activities near urban areas, protected animal habitats, sensitive historic buildings, water protection zones, pipelines, etc. While mechanical excavation is often longer lasting and more expensive, in some cases it may adequately replace blasting, where the applicability of mechanical excavation methods greatly dependent on the rock mass characteristics which should excavate. This paper provides practical examples of using existing methods for the assessment of the applicability of excavation technologies. In order to minimize the project impact on the environment, mechanical excavation was applied in some cases. In one case, the blasting could not be avoided, but controlled careful blasting techniques were applied.
Bibliografija: str. 38.
Summary.
Keywords: Iskop -- Mehanički iskop -- Miniranje -- Utjecaj na okoliš